[tex]a^2-b^2=(a-b)(a+b)[/tex]
This formula will be useful in helping us factor this.
[tex]49x^{16}-16y^{64}[/tex]
This is the equation that we are going to factor.
Let's first change this equation to have the form [tex]a^2-b^2[/tex]
In order to do that, here are two important exponent rules that was used.
[tex](a^b)^c=a^{bc}[/tex]
[tex](ab)^c=a^c b^c[/tex]
With those rules, we can change the equation into the following:
[tex](7x^8)^2-(4y^{32})^2[/tex]
Refer back to the formula I showed in the beginning of this answer.
[tex]a^2-b^2=(a-b)(a+b)[/tex]
[tex](7x^8)^2-(4y^{32})^2=(7x^8-4y^{32})(7x^8-4y^{32})[/tex]
Thus, your answer is the first choice. Hope this helps! :)